The Orbits of all Groups of Order 24 - Salih, Haval M. Mohammed; Jund, Asaad A.; Rasul, Tahsin I. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Let be a finite group of order and . In this paper, we provide the associated generalized conjugacy class graph for via computing the probability of the set which fixes by an element of . Several properties of these graphs are given. We achieve these results with the aid of the GAP-Software (Groups, Algorithms and programming).
Keywords: Orbit; Probability; Generalization; Conjugacy Class Graph